Ketangkasan Strategis sebagai Penggerak Ketahanan Organisasi Jangka Panjang - Nur Abdillah (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
Organizations increasingly operate under heightened uncertainty driven by environmental turbulence, recurring crises, and market–technology disruptions that challenge not only survival but also sustained adaptation and transformation. This article aims to develop a conceptual synthesis explaining how strategic agility functions as a driver of long-term organizational resilience and to propose an integrative model that can guide future empirical testing. The study adopts a qualitative, systematic literature review (SLR) approach, drawing on reputable peer-reviewed journal articles and scholarly sources addressing agility, resilience, and dynamic capabilities. Data were analyzed through thematic coding and conceptual mapping to extract core definitions, key dimensions, causal mechanisms, and boundary conditions shaping the agility–resilience relationship. The synthesis identifies four recurring agility dimensions—strategic sensing, fast decision-making and resource fluidity, strategic reconfiguration, and stakeholder agility—linking them to long-term resilience through mechanisms such as early warning and risk mitigation, rapid resource reallocation for operational continuity, continuous learning and capability renewal, and business model renewal. The relationship is stronger under high turbulence, mature digital and analytics capabilities, psychologically safe and collaborative cultures, balanced structural design (centralization–decentralization), and industry/regulatory contingencies. The article contributes an integrative framework and research propositions clarifying mechanisms and contextual effectiveness, while offering managerial implications for designing sensing routines, decision governance, resource mobility, learning systems, and renewal agendas.